The Effect of Starfruit Leaf Extract (Averrhoa bilimbi) on the Histology of Testes in Mice (Mus musculus) Exposed to Monosodium Glutamate (MSG) - Savira Ayunda Rakhmanira; Huda, Zainul; Rohmah, Meisya Putri Maulida; Sri Rahayu; Aris Soewondo; Agung Pramana Warih Marhendra (Biotropika: Journal of Tropical Biology, 2025)
This study analysed the effect of starfruit leaf extract (SL) on the testicular histology of mice exposed to MSG. This study used 25 male mice with a body weight of 25-30 grams and an age of 3-4 weeks. Mice were grouped into five groups: K(-) (healthy male mice), K(+) (male mice induced with MSG 4 mg/gBW), P1, P2, and P3 (male mice induced with MSG and SL extract (A. bilimbi) 250mg/kgBW, 500mg/kgBW, 750mg/kgBW for 21 days). Following the completion of the treatment, the mice were euthanised via cervical dislocation, and the testicular organs were collected. The left testicular organ was used for histological observation of the testes, with parameters including the percentage of spermatogenic cells, Leydig cells, seminiferous tubule diameter, and germinal epithelium thickness. The right testicular organ and SL extracts were tested for antioxidant activity using the DPPH method. Data was analysed using the SPSS program with one-way ANOVA and Mann-Whitney tests. These results indicate that the administration of SL extract at a dose of 750 mg/kgBB can increase testicular weight, seminiferous tubule diameter, germinal epithelium thickness, number of spermatogenic cells, and Leydig cells due to MSG exposure.  The results of the testicular antioxidant capacity test showed the highest %inhibition of 45.65% at the first dose.